Human Foramen Magnum Area and Posterior Cranial Fossa Volume Growth in Relation to Cranial Base Synchondrosis Closure in the Course of Child Development. Issue 5 (23rd June 2016) - Coll, Guillaume; Lemaire, Jean-Jacques; Di Rocco, Federico; Barthélémy, Isabelle; Garcier, Jean-Marc; De Schlichting, Emmanuel; Sakka, Laurent
Abstract: BACKGROUND: To date, no study has compared the evolution of the foramen magnum area (FMA) and the posterior cranial fossa volume (PCFV) with the degree of cranial base synchondrosis ossification. OBJECTIVE: To illustrate these features in healthy children. METHODS: The FMA, the PCFV, and the ossification of 12 synchondroses according to the Madeline and Elster scale were retrospectively analyzed in 235 healthy children using millimeter slices on a computed tomography scan. RESULTS: The mean FMA of 6.49 cm 2 in girls was significantly inferior to the FMA of 7.67 cm 2 in boys ( P <.001). In both sexes, the growth evolved in a 2-phase process, with a phase of rapid growth from birth to 3.75 years old (yo) followed by a phase of stabilization. In girls, the first phase was shorter (ending at 2.6 yo) than in boys (ending at 4.33 yo) and proceeded at a higher rate. PCFV was smaller in girls ( P <.001) and displayed a biphasic pattern in the whole population, with a phase of rapid growth from birth to 3.58 yo followed by a phase of slow growth until 16 yo. In girls, the first phase was more active and shorter (ending at 2.67 yo) than in boys (ending at 4.5 yo). The posterior interoccipital synchondroses close first, followed by the anterior interoccipital and occipitomastoidal synchondroses, the lambdoid sutures simultaneously, then the petro-occipital and spheno-occipital synchondroses simultaneously. CONCLUSION: The data provide a chronology of synchondrosis closure. We showed that FMA and PCFV are constitutionally smaller in girls at birth ( P ⩽.02) and suggest that a sex-related difference in the FMA is related to earlier closure of anterior interoccipital synchondroses in girls ( P =.01).